(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
An effective way of writing is mandatory in the current arena. The students need to acquire the skill in order to fetch a successful profession. In the work place, the students those who excel at writing skills are easily get attracted. The college students are in need to write well if it comes in writing notes, emails, reports and project proposal. Task-based method is a way of providing chances for learning in a natural way. It is proven that it reaches students in developing the writing skills. It would surely keep up the learners’ interest and support them to obtain their goal. Various language teachers and researchers have a strong belief that engaging students through a series of task will present more chances to accomplish the writing competence to a greater extent. This paper focuses on the review of writing skills, different methods and approaches of language teaching especially on TBLT